Mediating Effect of Attitude on the Determinants of Financial Misselling of Life Insurance Products in India - Shetty, Ankitha; Basri, Savitha (Prabandhan: Indian Journal of Management, 2021)
This study attempted to empirically validate a comprehensive model that combines individual traits, market competition, and organizational climate affecting the financial misselling by life insurance sales agents from an Indian perspective. The study adopted a cross-sectional design to collect survey data from 825 full-time insurance agents employed in life insurance companies in Karnataka state in South India. We found a positive relationship between misselling and ethical climate, indicating that salespeople’s perceptions might be changed by ethical codes, policies, or training but not their ethical behavior. Moreover, high-self monitors acting opportunistically to corner the sales by adopting dishonest sales practices indicated an instrumental ethical dimension. We also showed that competitive intensity positively influenced agents to exhibit financial misselling. Also, financial misselling increased when insurance companies designed varieties of complex products and exerted too much supervisory pressure on agents to amplify sales. Therefore, the working environment should enforce and promote a code of ethics that fosters an ethical attitude and hampers high self-monitors from pursuing individual interests at customers’ expense. There is a need to manage ethical and competitive climate and supervisors’ actions in reducing ethical conflicts and improving sales performance.